The Effect of Accounting Information Technology On Report Quality Finance In Sharia Bank In Parepare City - Burhanuddin; Semaun, Syahriah; Wahyuni Nur, Sri (Islamic Financial And Accounting Review, 2022)
BPK's findings on the financial statements show that there are still many agencies that have not presented the data that is presented inappropriately and that there are still many irregularities that have been found. To be able to produce quality financial reports, competent human resources are needed in the field of financial management by utilizing information technology, but not all human resources are able to understand and apply accounting information technology. This study aims to determine the effect of the use of accounting information technology on the quality of financial reports. This research uses a quantitative approach with associative research type. The population in this study is a Sharia Bank in the City of Parepare. Sampling technique using purposive sampling method. The sample in this study were employees of Islamic banks in the city of Parepare, the number of questionnaires that were processed in this study were as many as 30 questionnaires. Data analysis using simple linear regression analysis. The results of the study with simple linear regression analysis show that the performance of accounting information technology has a positive and significant effect on the quality of financial statements. This is indicated by the value of the t count of 4.728 greater than t table 2.048 with a coefficient test value of the determination (R2) of 0.444 and has a pearson correlation value of 0.666 or a strong correlation with a positive form of relationship.